Evaluasi Karakteristik Fisik Kimiawi Perairan Situ Cibuntu, Kabupaten Bogor, Jawa Barat - Aiman Ibrahim; Siti Aisyah; Ira Akhdiana; Lukman; Aldiano Rahmadya; Novi Mayasari (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Pond Cibuntu is one of the urban ponds located in Bogor Regency, West Java Province. With a maximum surface area of 2.11 ha and maximum depth of 1.20 m, the pond serves as retention pond and recreational fishing. Ponds in urban areas can be disturbed due to siltation, land conversion, and anthropogenic activities that can influence the physico-chemical conditions of the waters. The aims of this study was to evaluate the physico-chemical properties of the Pond Cibuntu as basis for freshwater ponds management. This study was conducted from September to December 2018 at five observation stations. The results of this study showed that the parameters of water temperature, TDS, pH, DO, and total phosphorus still meet the class III of water quality standards according to Government Regulation Number 82 of 2001. The value of total nitrogen and total phosphorus indicates Pond Cibuntu which is eutrophic to hypereutrophic.